Frequency of Urinary Tract Infection in Children with Cerebral Palsy - Yousaf Kakar, Sana Bushra, Maryam Shoaib, Mehboob Ul Haq, Noor Ul Haram Khattak, Sumaya Fatima, Muhammad Ahtisham Azhar, Muhammad Awais Naseer, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The incidence of cerebral palsy ranges from 2 to 25 per 1000 live birth. Both low birth weight and premature birth are significant contributors to the development of cerebral palsy. According to various studies, children with cerebral palsy are susceptible to urinary tract infections Objective: To find out the frequency of urinary tract infection in children with cerebral palsy Methodology: This cross sectional study was carried out at the Pediatrics department Sandeman Provincial Hospital Quetta from January 2022 to July 2022. The research included all CP children who met the inclusion requirements and reported a fever. Two clean midstream urine samples were collected from each child and forwarded to the hospital laboratory for the purpose of identifying UTIs. All the information was entered into a predesigned proforma. For the analysis of data, IBM SPSS version 23 was used. Results: In this study, totally 60 children were included. The male children in our study were 42 (70%) while female children were 18 (30%). The mean age (±SD) was 8 (±2.15) years. The overall prevalence of urinary tract infection in children with cerebral palsy was 20 (33.33%). Conclusion: Our study concluded that the prevalence of urinary tract infection in children with cerebral palsy was high. This high prevalence might be due to immobility. Keywords: Frequency; Urinary tract infection; cerebral palsy